Sonic the hedgehog : complete series [videorecording (DVD)] (Sonic the Hedgehog., 2023)
Sonic is back on Planet Mobius, using his supersonic speed and teenage irreverence to thwart the comedically despicable Dr. Robotnik. Sonic₂s idolizing little buddy, Tails, tags along on every fast-action, gag-driven adventure.